Strategi Inovasi Produk Berbasis Bahan Lokal di Era 4.0 Untuk Meningkatkan Ekonomi Desa Gadungan Kecamatan Wates Kabupaten Kediri - Esti Rahayuningtyas, Tri; Widyatmoko, Widyatmoko; Pramudyawardana Kusuma Negara, Wana; Pradipta Himawan, Mahadika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Gadungan Village, located in Wates District, Kediri Regency, is a major producer of sweet potatoes, with challenges including sandy soil and reliance on rainfed agriculture. This study aims to evaluate the village’s potential for developing sweet potato-based products, such as sweet potato brownies, and explore solutions to optimize its utilization through training and mentoring. The main issues identified include the limited use of sweet potatoes with traditional methods and a lack of knowledge on innovative processing and marketing through social media. This research employs a qualitative approach using a case study method, with data collected through interviews, observations, and documentation. The results indicate that the training successfully enhanced participants' skills in making sweet potato brownies and understanding product marketing via social media. This intervention is expected to increase the community's income and optimize the use of local resources. Prior to the training, only 40% of participants understood how to develop innovative and attractive product variants. After the training, this figure increased to 80%. The sustainability of the business post-training is ensured through ongoing support in production management, finance, and digital-based marketing.